Identifying misconceptions in Plantae classification using a four-tier diagnostic test - Al Fitrah, Ikhtiar Amadea; Wisanti, Wisanti; Zubaidah, Siti (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2026)
Misconceptions are understandings that contradict scientific concepts. This study aims to identify misconceptions among 11th-grade students in Surabaya regarding the Plantae classification based on the results of the four-tier diagnostic test (KlasPlant-4T). This study is a descriptive survey to objectively describe misconceptions and level of misconceptions. The research sample consisted of 115 11th-grade students from 9 high schools in Surabaya who were selected using simple random sampling technique. The instrument used was KlasPlant-4T, consisting of 10 questions Plantae classification, arranged in four levels. The research stages included the preparation and implementation of the KlasPlant-4T. The KlasPlant-4T test resulted in validity score of 90% (highly valid) and Cronbach alpha reliability score of 0.69 (reliable). Data analysis used simple statistics, including category percentages and levels of misconception. The results of this study showed that students’ conceptual profiles consisted of the conceptual understanding (23%), partial understanding (34%), misconceptions (24%), and not understanding (19%). The levels of misconception were low (70%), moderate (23%), and high (7%). The misconceptions found included the classification of Gnetum gnemon (38%), rules for writing scientific nomenclature (29%), and characteristics of members of the Plantae Kingdom (13%). Thus, KlasPlant-4T tests can be recommended to help teachers in designing the learning that minimizes misconceptions in Plantae classification.